ANALISIS KAUSALITAS PERTUMBUHAN EKONOMI, KEMISKINAN, DAN KETIMPANGAN PENDAPATAN DI SUMATERA BARAT - Riri Agustina Fratiwi; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This stuudy”explains the analysis causality of economic”growth poverty, and income”inequality in west”sumatera. The method used is to a panel regression model. This data uses a combination of time series data”from 2013-2017, which consists of 19 city districts. Data obtained from BPS annual”report (Statistics Indonesia). The”results of”this study show that (1) there is no”causall relationship”between”economic”growth and poverty (2) there is a causal relationship”between”economic”growth”and inequality (3) there is no causal relationship”between poverty”and income”inequaality.